G Protein–Coupled Estrogen Receptor Production Using an Escherichia coli Cell‐Free Expression System. (19th June 2019) - Souza, Samson A.; Kurohara, Dane T.; Dabalos, Chester L.; Ng, Ho Leung
Abstract: Heterologous expression of the G protein–coupled estrogen receptor (GPER) comes with a suite of challenges intrinsic to membrane proteins. This receptor's low expression levels and tendency to form insoluble aggregates in Escherichia coli and yeast make it a difficult receptor‐target to study. In this unit, we detail steps to produce monomeric GPER using a precipitation‐based cell‐free system. We provide information on the DNA construct for expression, the pipetting scheme for the reaction supplements to generate a master mix, and the cell‐free reaction setup. In the last portion of this unit, we outline steps for solubilization and purification, and we provide a viable method for qualitatively observing functionality by liquid chromatography–mass spectrometry detection. © 2019 by John Wiley & Sons, Inc.